Sound Capture System and Spatial Filter for Small Devices - Tashev, Ivan; Mihov, Slavy; Gleghorn, Tyler; Acero, Alex (Proceedings of Interspeech 2008, 2008)
Usage of cellular phones and small form factor devices as PDAs and other handhelds has been increasing rapidly. Their use is varied, with scenarios such as communication, internet browsing, audio and video recording just to name a few. This requires better sound capturing system as the sound source is already at larger distance from the device’s microphone. In this paper we propose sound capture system for small devices which uses two unidirectional microphones placed back-to-back close to each other. The processing part consists of beamformer and a non-linear spatial filter. The speech enhancement processing achieves an improvement of 0.39 MOS points in the perceptual sound quality and 10.8 dB improvement in SNR.